Chalk and Talk Versus Powerpoint: Perception among Medical Students (Medico Legal Update, 2021)
Introduction: The emerging technologies made by day changing the techniques of teaching medicaleducation. The teaching technique has changed since the last decade from the old traditional techniqueof chalk and talk (CNT) to a newer technique of Power-point presentation (PPT) to the video classroomsconverting the whole traditional environment of the classrooms. This paper aims to access the perception ofthe medical students about these two instructional method.Materials and Method: In this study cross-sectional descriptive survey was used. Medical students wereselected through non-probability convenient sampling. The data were collected using a questionnaire-basedsurvey about their views and perception of two method of lecture delivery, viz., PPT presentation, and usinga chalkboard. For each of the two method, the students were asked to rank twelve comments on a four-pointscale: strongly agree, agree, disagree, or strongly disagree. The data was analyzed using SPSS version 16and the results expressed as proportions.Results: In our study where more than 97% of our study respondents emphasized the value of chalk andtalk and declared it as the more effective and useful teaching tool in their learning experience compared toPowerPoint (86%) and recommended it for teaching.Conclusion: Both CNT, as well as PPT, are the effective method for medical education and both can be usedin combination for the effective delivery of classroom sessions.